The role of video-assisted thoracoscopy in the treatment of isolated closed chest trauma - V. G. Kotandzhian; E. A. Tarabrin; Sh. N. Danielian; A. K. Shabanov; I. E. Popova; S. A. Korneeva; K. M. Rabadanov; E. V. Tatarinova; E. B. Nikolaeva (Вестник хирургии имени И.И. Грекова)
The objective was to evaluate the effectiveness and safety of video-assisted thoracoscopic surgery for closed chest trauma and to determine the most favorable terms for performing surgical intervention in case of complicated closed chest injury.METHODS AND MATERIALS. The study included 95 patients who underwent video-assisted thoracoscopy (VATS) for closed chest trauma. Group I – operated within the first 5 days from the moment of injury; group II – operated within 5–10 days after injury; group III – operated later than 10 days after injury.RESULTS. Performing thoracoscopic intervention within the first 5 days after the injury significantly reduces the incidence of complications such as pneumonia, pleurisy, empyema. VTS allows safely and effectively performing various surgical procedures in case of complicated closed chest trauma, and diagnosing diaphragm injuries.CONCLUSION. Indications for video-assisted thoracoscopy should be set as early as possible.